Nosocomial treatment-induced neuropathy of diabetes : an important cause of painful and autonomic neuropathy in hospitalized diabetes mellitus patients - Koh, Jasmine Shimin (2021)
Treatment-induced neuropathy of diabetes (TIND) is an acute painful autonomic small-fiber neuropathy that develops following an abrupt improvement in glycaemia control. Recent reports suggest TIND is a significant problem in tertiary neuropathy clinics. TIND in hospitalized patients with poor initial glycaemia control, that we refer to as nosocomial TIND, has not been well-studied. We describe the demographic, clinical features and indices of glycaemia control in 5 consecutive nosocomial TIND patients. TIND was defined using recently published criteria. Pre-meal capillary blood glucose recordings performed during the period of HbA1c decline was used to calculate glycaemic variability. All the nosocomial TIND patients were hospitalized for prolonged periods for serious medical conditions that warranted good glycaemia control, namely severe sepsis, diabetic ketoacidosis, stroke, heart failure and traumatic head injury. They had raised, double-digit, HbA1c levels at admission that subsequently dropped precipitously with tight in-patient glycaemia control protocols. These patients had multiple, largely asymptomatic, hypoglycaemic episodes. Glycaemic variability also appeared to be high in this cohort. TIND may be a significant cause of morbidity in hospitalized diabetic patients with poor glycaemia control. Not all patients developed both autonomic and painful neuropathies, raising the possibility of forme-fruste TIND.